Biblical Interpretation in Greek Orthodox Eco-theology - LI , Lin (Journal of Research for Christianity in China (JRCC), 2022)
This paper presents an overview of the core ecological views of the Greek Orthodox Church based on biblical interpretation through the biblical references in the environmental encyclical of Ecumenical Patriarch of Constantinople Bartholomew, a representative figure of the Greek Orthodox Church, and the interpretation of the corresponding biblical ecological theological views by Greek Orthodox theologians. These core insights include: the iconic perspective of the Greek Orthodox Church's experience of nature in the eternal dimension of the Eucharist, which holds that all things have the presence of God's power; that ecological catastrophe arises from the reproduction of human sin, the progressive failure of the natural order to glorify God through the transmission of the firstborn's sin of rebellion against God from generation to generation,  repentance is therefore a prerequisite for ecological endeavour; that the reconciliation brought about by the crucifixion of Jesus involves not only man and God, but also the earth; that imitating the love of Christ and loving God is the driving force behind Christian concern for ecology; that in the eschatological dimension, the Church is also confronted with the problem of whether it has taken care of the weak creation entrusted to it by God and how it will pay its debt; that the Church has the important role of prophetic teaching and cosmic priesthood in contemporary ecological ministry.